Study on the microstructure evolution and strengthening mechanism of Cu-Ni-Si alloy after two-stage rolling and aging - Yunqi Shan; Yanmin Zhang; Chaomin Zhang; Jiang Feng; Baohuan Huang; Shiheng Zhao; Kexing Song (Materials & Design)
With the development of high-end integrated circuits toward higher integration and ultra-thin designs, the comprehensive performance requirements for Cu-Ni-Si alloys as lead frame materials continue to increase. In this paper, the microstructure of the alloy is optimized by adjusting the deformation and aging parameters during the two-stage rolling process to enhance its performance and reveal the underlying mechanism. It was found that the hardness and strength of the alloy were enhanced while the conductivity remained unchanged or even slightly improved. With an increase in two-stage rolling deformation, the dislocation density of the alloy increases, promoting the rapid precipitation of the second phase and a reduction in grain size. The improvement in strength is primarily attributed to the synergistic effects of dislocation strengthening, precipitation strengthening, and grain boundary strengthening. In addition, with an increase in deformation, the texture strength of Cube, S, and Copper gradually decreases, while that of Brass increases significantly. This texture transformation is positively correlated with the comprehensive properties of the alloy.